2004
DOI: 10.1111/j.1464-5491.2004.01299.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of secondary diabetes mellitus with acromegaly improved by pioglitazone

Abstract: Pioglitazone treatment might be considered as a choice for similar cases of diabetes secondary to acromegaly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Pioglitazone has also been successfully used as antidiabetic treatment in patients with acromegaly, as shown in two case reports ( 156 ). Preclinical findings showed that thiazolidinediones also reduced circulating GH and IGF-1 levels and GH pituitary cell hormone secretion ( 157 , 158 ).…”
Section: Acromegalymentioning
confidence: 99%
“…Pioglitazone has also been successfully used as antidiabetic treatment in patients with acromegaly, as shown in two case reports ( 156 ). Preclinical findings showed that thiazolidinediones also reduced circulating GH and IGF-1 levels and GH pituitary cell hormone secretion ( 157 , 158 ).…”
Section: Acromegalymentioning
confidence: 99%
“…According to a clinical study of 70 patients with acromegaly and secondary DM, 15.7% of patients are controlled on diet, 65.7% of patients receive metformin as monotherapy or in combination with other oral anti-diabetic medications and 21.5% of patients are insulin-treated, with all exhibiting excellent glycemic control (mean HbA1c = 6.4%) and low prevalence of diabetic microangiopathy [ 138 ]. Furthermore, thiazolidinediones have been demonstrated to achieve optimal glycemic control and allow insulin discontinuation in 2 case reports [ 139 , 140 ]. Moreover, a recently-published case series in 9 patients receiving sodium-glucose-co-transporter 2 inhibitors (SGLT2is) shows 1% decrease in HbA1c without adverse events [ 141 ].…”
Section: Treatment Of Secondary and Pasi-induced Dm In Acromegalymentioning
confidence: 99%
“…В литературе описаны два клинических случая применения у больных с акромегалией тиазолидиндионов, назначение которых обеспечило оптимальный гликемический контроль и позволило отменить инсулинотерапию [81,82]. Гамма-рецептор, активирующий пролиферацию пероксисом (PPARγ), экспрессируется в соматотропиномах, пролактиномах и гонадотропиномах, и по данным экспериментальных исследований тиазолидиндионы ингибируют секрецию ГР и пролактина, а также рост опухолевых клеток аденогипофиза in vivo и in vitro [83].…”
Section: лечение сахарного диабета при акромегалииunclassified